Mural by Robert Tressell (1905)
1905 1880-1914 "Mural by Robert Tressell" [T0465.jpg], 1905 A renovated panel from a mural painted in 1905 by Robert Noonan (Tressell) for St Andrews's church, Queen's Road, Hastings. This panel was saved by Tressell enthusiasts before the church was demolished in 1970. Following a successful appeal, the mural was restored and can now be seen in Hastings Museum and Art Gallery.